Behçet's Disease Under Microbiotic Surveillance? A Combined Analysis of Two Cohorts of Behçet's Disease Patients - van der Houwen, Tim B.; van Laar, Jan A. M.; Kappen, Jasper H.; van Hagen, Petrus M.; de Zoete, Marcel R.; van Muijlwijk, Guus H.; Berbers, Roos-Marijn; Fluit, Ad C.; Rogers, Malbert; Groot, James; Hazelbag, C. Marijn; Consolandi, Clarissa; et al. (Frontiers in Immunology, 2020)
Background: In Behçet’s disease (BD), an auto-inflammatory vasculitis, an unbalanced gut microbiota can contribute to pro-inflammatory reactions. In separate studies, distinct pro- and anti-inflammatory bacteria associated with BD have been identified. Methods: To establish disease-associated determinants, we performed gut microbiome profiling in BD patients from the Netherlands (n=19) and Italy (n=13), matched healthy controls (HC) from the Netherlands (n= 17) and Italy (n=15) and oral microbiome profiling in Dutch BD patients (n=18) and HC (n=15) by 16S rRNA gene sequencing. In addition, we used fecal IgA-SEQ analysis to identify specific IgA coated bacterial taxa in Dutch BD patients (n=13) and HC (n=8). Results: In BD stool samples alpha-diversity was conserved, whereas beta-diversity analysis showed no clustering based on disease, but a significant segregation by country of origin. Yet, a significant decrease of unclassified Barnesiellaceae and Lachnospira genera was associated with BD patients compared to HC. Subdivided by country, the Italian cohort displays a significant decrease of unclassified Barnesiellaceae and Lachnospira genera, in the Dutch cohort this decrease is only a trend. Increased IgA-coating of Bifidobacterium spp., Dorea spp. and Ruminococcus bromii species was found in stool from BD patients. Moreover, oral Dutch BD microbiome displayed increased abundance of Spirochaetaceae and Dethiosulfovibrionaceae families. Conclusions: BD patients show decreased fecal abundance of Barnesiellaceae and Lachnospira and increased oral abundance of Spirochaetaceae and Dethiosulfovibrionaceae. In addition, increased fecal IgA coating of Bifidobacterium, Ruminococcus bromii and Dorea may reflect retention of anti-inflammatory species and neutralization of pathosymbionts in BD, respectively. Additional studies are warranted to relate intestinal microbes with the significance of ethnicity, diet, medication and response with distinct pro- and inflammatory pathways in BD patients.